Penerapan Strategi Pembelajaran Aktif Untuk Meningkatkan Pemahaman Konsep Matematika Siswa Madrasah Ibtidaiyah: Penelitian - Nashaihul Naima; Artisya Vinolian A; Luthfi Ismail; Deztyka Luthfiah F; Ismi Nur H; Praptiningsih (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to describe the learning strategies implemented in the teaching process and to examine how students respond to these strategies. The focus of the research is directed toward learning activities that emerge when the teacher employs simple learning media and group work methods to enhance students’ understanding of the subject matter.This research uses a descriptive qualitative method. According to Sugiyono, qualitative research is used to understand phenomena deeply through data collection in natural settings. Data were collected through observation, interviews, and documentation. The validity of the data was tested using source triangulation, by interviewing three different participants with the same questions (such as the subject teacher, one student, and one group leader). Additionally, technique triangulation was applied by comparing data from interviews, observations, and documentation (such as students’ scores, photos of learning activities, and learning notes). All data were analyzed through data reduction, data display, and conclusion drawing.The findings show that the teacher applied learning strategies through the use of a ruler as a simple instructional medium, group division, and group presentations. To ensure students’ understanding, the teacher provided guidance by moving around the class and asking each group about the material. These strategies proved effective in helping students become more active, engaged in discussions, and gradually understand the learning material through collaborative group work.